ANALISIS PEMASARAN CABAI RAWIT (Capsicum frutescens L..) DI KECAMATAN BARUSJAHE KABUPATEN KARO - Fandri Siburian; Andi Pranata Sembiring (JURNAL AGROTEKNOSAINS, 2019)
Analysis of Marketing of Rawitic Chili (Capsicum frutescens L.) in Barusjahe District, Karo Regency. The method of determining farmer samples was carried out in Simple Random Sampling where the number of chili farmers in the village was 80 kk (head of household), and 20 kk was taken for samples. Data collected in this study consisted of primary data and secondary data. Primary data is obtained through direct interviews with farmers and traders using questionnaires that have been prepared previously. Secondary data was obtained from the Karo District Agricultural Service, Channels of cayenne marketing in Sikab Village were divided into two, namely cayenne which was sold to the market (first channel non Ped. Regency collector with a capacity of 74.8 tons) and cayenne sold to the market (second channel through Ped. Collector District with a capacity of 22.6 tons. The results showed that the marketing of cayenne in Karo District has Components of Cost, Price Spread and Share of Cayenne Margin through Marketing Channels I per One Pick up (1.5 tons) Buy Prices Raw Chili from Farmers Rp. 15,000 / kg @ 1,500 kg = 30,000,000, Consumer purchase price Rp. 30,000 / kg @ 1500kg = 45,000,000, - so the Total Profit Margin is 19,364,435. Component Cost, Price Spread and Share of Cayenne Margin through Marketing Channels II per One Pick up (1.5 tons) Buy Prices for Raw Chili from Farmers Rp. 15,000 / kg @ 1,500 kg = 22,500,000, Consumer Purchase Price Rp. 30,000 @ 1500 kg = 45,000,000 so Total Profit Margin 19,184,740, -. From the results above, we can see that the marketing of cayenne through channel I is more efficient than marketing chili through channel II. This happens because the marketing efficiency value in channel I is smaller than the marketing efficiency value on channel II.